2019
DOI: 10.1111/nmo.13546
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the physiology of gastric emptying

Abstract: There have been many recent advances in the understanding of various aspects of the physiology of gastric motility and gastric emptying. Earlier studies had discovered the remarkable ability of the stomach to regulate the timing and rate of emptying of ingested food constituents and the underlying motor activity. Recent studies have shown that two parallel neural circuits, the gastric inhibitory vagal motor circuit (GIVMC) and the gastric excitatory vagal motor circuit (GEVMC), mediate gastric inhibition and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
173
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(188 citation statements)
references
References 121 publications
(255 reference statements)
2
173
0
13
Order By: Relevance
“…Gastric emptying is one of the critical factors affecting postprandial glycaemia and food intake, which is a complex interplay involving gastric, intestinal and central neuronal and humoral mechanisms. 11 The role of GLP-1 in GE has been intensively studied. 12 Research on GIP and its effect in GE is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric emptying is one of the critical factors affecting postprandial glycaemia and food intake, which is a complex interplay involving gastric, intestinal and central neuronal and humoral mechanisms. 11 The role of GLP-1 in GE has been intensively studied. 12 Research on GIP and its effect in GE is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric motility is regulated by neural circuits that affect smooth muscle contractility. Current studies have shown that the gastric inhibitory vagal motor circuit that comprises DMX-located preganglionic cholinergic neurons and postganglionic neurons of the myenteric plexus also mediates inhibition of gastric emptying [53]. Vagal stimulation of the myenteric neurons relaxes the smooth muscles by releasing VIP and NO [54].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of gastric emptying, which depends on ingested food volume, osmolality, chemical composition, and caloric content, is an important determinant of digestion and nutrient absorption in small intestine (45). Liquids generally exit the stomach much faster than solid foods.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of gastric emptying of carbohydrates and simple sugars is particularly important for postprandial elevations in blood glucose (16). In the clinical setting, measurement of gastric emptying uses a [ 13 C] or [ 99m Tc]-DTPA-labeled egg white meal with breath testing or scintigraphy readouts, respectively (45). [ 13 C] breath testing following an egg white meal is also used in mice, with time to empty half of the stomach contents generally between 60 and 90 min (38,46).…”
Section: Discussionmentioning
confidence: 99%